PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY DENGAN E-SATISFACTION SEBAGAI VARIABEL INTERVENING (STUDI PADA PENGGUNA SHOPEEFOOD DI KOTA BANDUNG) - Julyani, Amanda; Setiawardani, Maya (Buletin Studi Ekonomi, 2024)
The development of technology in Indonesia, has driven the growth of the OFD (Online Food Delivery) market. ShopeeFood is an OFD service that needs to compete because it faces challenges and complaints from consumers. This study aims to determine and analyze the effect of e-service quality on e-loyalty through e-satisfaction for ShopeeFood users in Bandung City. The research method is quantitative with an explanatory research approach. Sampling using non probability sampling technique with purposive sampling. Data collection through an online survey using a questionnaire with a Likert scale and a sample of 214 respondents was obtained. The data analysis technique used is path analysis and sobel test with the help of IBM SPSS 25. The results showed that e-service quality has a positive and significant effect on e-satisfaction, e-service quality has a significant positive effect on e-loyalty, e-satisfaction has a significant positive effect on e-loyalty, and e-service quality has a significant positive effect on e-loyalty through e-satisfaction as an intervening variable. Therefore, to achieve e-loyalty, ShopeeFood needs to improve e-service quality that meets user expectations.